UNSCR 1325 Reload: Analyzing the implementation of a gender perspective in NATO countries and Australia - Palomo, Jesús (Colección de libros electrónicos de ULoyola, 2017)
Since its passage, United Nations Security Council Resolution (UNSCR) 1325 has been advocated and adopted by a range of actors-including international Non-Profit Organizations, International Organizations, United Nations agencies, and some national governments, showing the importance of integrating a gender perspective into the process of maintaining international peace and security. Due to the implementation of gender mainstreaming in national and international peace and security operations, women?s presence in the armed forces, or other decision positions, is increasing but at a very slow pace and still with lots of operational and strategic actions needed. There is a great need of women?s participation in Armed Forces, from a quantitative and qualitative point of view, for efficiency purposes. Consequently, this book presents the main analyses and results of the UNSCR 1325 Reload Project, developed by the Rey Juan Carlos University (Spain), the Australian Human Rights Commission and the Australian Defense Force, with the support of the NATO Science for Peace and Security. A quantitative evaluation of the number of women in NATO member?s Armed Forces, as well as of the specific legislation, policies and actions is presented along with detailed recommendations to improve the participation of women in order to have more efficient and effective Armed Forces.